EVALUATION OF THE AIR QUALITY IN DENTAL LABORATORY - Diana Diaconu-Popa (Romanian Journal of Oral Rehabilitation, 2018)
During the technological steps of dental prostheses realization, the technician is exposed to various noxes that may affect his health. The aim of our study was a quantitative analysis of a dust released into the dental laboratory during the dental prostheses processing and finishing and to determine the microbial charge of these powders. The air samples were taken fromthe laboratory for 7 days, 8 hours a day and the powders’ concentration was performed with HPC 601 Airborne Particle Counter. To determine the microbiological contamination of the air it was used the collection by sedimentation method. The data were recorded before, during and after the prostheses were processed. The results obtained show a high degree of air pollution and contamination in the dental laboratory, which, although below the maximum allowed, may affect the health of the dental technician who is permanently exposed to these noxes by their cumulative effect.